The Neuroprotective Effect of Gugijihwang-Tang on Trimethyltin-Induced Memory Dysfunction in the Rat - Jung, Eun-Yee (Hindawi Publishing Corporation, 2013)
Gugijihwang-Tang (the herbal formula PM012), a decoction consisting of several herbs including Rehmanniae Radix Preparata, has been widely used as herbal treatment for dementia. In order to investigate the neuroprotective action of this prescription, we examined the effect of Gugijihwang-Tang on learning and memory using the Morris water maze and [F-18]FDG micro PET neuroimaging technique. After injection of trimethyltin (TMT, 8.0 mg/kg, i.p.), which is a potent toxicant that selectively kills cells in the central nervous system, rats were administered Gugijihwang-Tang (100 mg/kg, p.o.) daily for two weeks, followed by the Morris water maze tasks and [F-18]FDG micro PET neuroimaging. In Gugijihwang-Tang administered TMT-treated rats, they showed improved learning and memory abilities in water maze tasks and glucose metabolism, suggesting that Gugijihwang-Tang plays effectively positive role in the improvement of brain function including learning and memory after TMT-induced neurodegeneration. Taken together, our results suggested that the Gugijihwang-Tang should be useful for developing strategies protecting nervous system and improving brain function.